Lymph Node Stromal Cells From Different Draining Areas Distinctly Regulate the Development of Chronic Intestinal Inflammation - Basic, Marijana; Peppermüller, Pia Pascale; Bolsega, Silvia; Bleich, André; Bornemann, Melanie; Bode, Ulrike; Buettner, Manuela (Frontiers in Immunology, 2021)
The balance between the responsiveness of the intestinal immune system and the gut environment is fundamental for the maintenance of intestinal homeostasis, which is required for an adequate recognition of entering antigens. The disruption of this homeostasis by exaggerated immune response to harmless antigens can lead to the development of intestinal disorders such as inflammatory bowel disease. Stromal cells are sessile non-hematopoietic cells that build the backbone of the lymph node, an important site for the immune response induction, but also contribute to immune response and tolerance induction. However, the knowledge about the role of stromal cells in the regulation of inflammatory responses is still limited. Therefore, in this study we analyzed the influence of stromal cells on the development of chronic intestinal inflammation. Here, we show that intestinal inflammation alters the immune activation of the mesenteric lymph node-derived stromal cells. Podoplanin+ and CD21/35+ stromal cells showed increased expression of MHC class II molecules, but CD106 expression on CD21/35+ cells was reduced. Stromal cells secreted cytokines and chemokines such as CCL7 and CXCL16 influenced the gut-homing phenotype and proliferation of CD4+ and CD8+ T cells. Furthermore, stromal cells of peripheral lymph nodes transplanted into the mesentery attenuated colitis severity in B6-Il10-/- mice. The reduced colitis severity in these mice was associated with increased expression of IL4 and distinct activation pattern of stromal cells derived from transplanted peripheral lymph nodes. Altogether, our results demonstrate that lymph node stromal cells impact development of chronic colitis via T cell induction. Moreover, lymph node stromal cells from different draining area due to neonatally imprinted processes distinctly regulate the induction of immune responses.